2014
DOI: 10.1186/1471-2407-14-777
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for disease-specific survival in 108 patients with Hürthle cell thyroid carcinoma: a single-institution experience

Abstract: BackgroundHürthle cell thyroid carcinoma (HCTC) is a rare disease. It is believed that it is more aggressive than follicular thyroid carcinoma. The aim of our study was to identify factors associated with disease-specific and disease-free survival.MethodsAltogether, 108 patients with HCTC (26 male, 82 female; median age 62 years; range 19–87 years) treated at our Institute from 1972 to 2011 were included in the present retrospective study. Data on age, clinical and histopathological factors, tumor stage, recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 29 publications
5
47
2
6
Order By: Relevance
“…El compromiso ganglionar en la literatura oscila entre 7 y 30% 4,6 . En la serie propia, la frecuencia de afección ganglionar laterocervical fue mayor del 40%.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…El compromiso ganglionar en la literatura oscila entre 7 y 30% 4,6 . En la serie propia, la frecuencia de afección ganglionar laterocervical fue mayor del 40%.…”
Section: Discussionunclassified
“…Se considera que el CCH es una enfermedad más agresiva y de peor pronóstico que el resto de los CDT, dada su propensión a originar metástasis ganglionares, diseminación a distancia y recaídas tardías 2,4,6 . El objetivo es comunicar la experiencia de dos centros oncológicos en el manejo de pacientes con diagnóstico histológico de CCH, el Instituto de Oncología Ángel H. Roffo y el Hospital de Oncología María Curie.…”
unclassified
See 1 more Smart Citation
“…Further evaluations revealed that unstable 53BP1 expression had a significant positive correlation with the levels of expression of Tumor protein 73. These data suggest a higher level of genomic instability in oncocytic FA compared with conventional FA, and a possible relationship between oncocytic FA and abnormal amplification of Tumor protein 73.Key words: Thyroid oncocytic tumor, 53BP1, DNA damage response, Genomic instability plasms of follicular cell origin predominantly, or entirely, composed of large polygonal cells with oxyphilic features related to the presence of eosinophilic and granular cytoplasm that is rich in mitochondria [1][2][3]. Encapsulated thyroid lesions with no evidence of capsular or vascular invasion and no nuclear features of papillary carcinoma are diagnosed as onco-…”
mentioning
confidence: 99%
“…Key words: Thyroid oncocytic tumor, 53BP1, DNA damage response, Genomic instability plasms of follicular cell origin predominantly, or entirely, composed of large polygonal cells with oxyphilic features related to the presence of eosinophilic and granular cytoplasm that is rich in mitochondria [1][2][3]. Encapsulated thyroid lesions with no evidence of capsular or vascular invasion and no nuclear features of papillary carcinoma are diagnosed as onco-…”
mentioning
confidence: 99%